Weekly versus three-weekly cisplatin as an adjunct to radiation therapy in high-risk stage I-IIA cervical cancer after surgery: A randomized comparison of treatment compliance - Chumworathayi B. (2014)
Objectives: To compare weekly and three-weekly cisplatin as an adjunct to radiation therapy in high-risk early-stage cervical cancer after surgery with regard to treatment compliance. Material and Method: From June 1st, 2003 to February 29th, 2004, the authors performed a randomized trial of radiotherapy in combination with two concurrent chemotherapy regimens - weekly or three-weekly cisplatin - in patients with high-risk cervical cancer FIGO stage I-IIA after surgery. Women with primary invasive squamous-cell carcinoma, adenocarcinoma, or adenosquamous carcinoma of the cervix were enrolled. The patients also had to have an absolute neutrophil count of at least 1,500 cells per cubic millimeter, a platelet count of at least 75,000 cells per cubic millimeter, a creatinine clearance higher than 40 milliliter per minute, and adequate hepatic function. All patients received external-beam radiotherapy according to a strict protocol. Patients were randomly assigned to receive one of two chemotherapy regimens: 75 mg per square meter of cisplatin on days 1, 22, 43 and 64 or every three weeks for 4 cycles (group 1) or 40 mg per square meter of cisplatin per week for six cycles (group 2). Results: The analysis included 40 women. The first group that received three-weekly cisplatin had a higher rate of incomplete and delayed treatments than the second group that received weekly cisplatin (p < 0.001 and p = 0.0236 respectively). The relative risks of delayed courses were 2.06 (95 percent confidence interval, 1.15 to 3.68) for group 1, compared with group 2. The toxicity-related incomplete treatments rate and G-CSF doses used were significantly higher in group 1 than in group 2. Conclusion: Concurrent chemoradiation with weekly cisplatin regimen has more complete treatment rate and less delayed courses than that with three- weekly cisplatin among women with high-risk cervical cancer after surgery.